Operating Capacity, Sales Growth, dan Operating Cash Flow Terhadap Nilai Perusahaan dengan Financial Distress Sebagai Variabel Intervening - Neezmadevi, Kallyana Tantri; Rahmiyati, Nekky; Rachmawati, Titiek (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This study examines the effect of operating capacity, sales growth, and operating cash flow on company value with financial distress as an intervening variable in transportation companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. This type of research is quantitative research. The sample population for this study are 12 transportation companies listed on the Indonesia Stock Exchange in 2017-2021 which have minus profits or have suffered losses for 2 (two) consecutive years. The method used in this research is Partial Least Square (PLS) version 4.0.9.3. The results of the study show that operating capacity has no significant effect on financial distress; operating capacity has a significant effect on firm value; sales growth has no significant effect on financial distress; sales growth has a significant effect on company value; operating cash flow has no significant effect on financial distress; operating cash flow has no significant effect on firm value; financial distress has no significant effect on firm value; financial distress is not able to moderate operating capacity on company value; financial distress is not able to moderate sales growth on company value; and financial distress is not able to moderate operating cash flow on firm value.